Rechargeable Batteries: Grasping for the Limits of Chemistry. Issue 14 (1st January 2015) - Berg, Erik J.; Villevieille, Claire; Streich, Daniel; Trabesinger, Sigita; Novák, Petr
Abstract : The demand for rechargeable batteries with high gravimetric and volumetric energy density will continue to grow due to the rapidly increasing integration of renewable energy into the global energy scheme. In terms of energy density, modern high-end rechargeable-battery technology is reaching its fundamental limits and no big advancement leaps in this field are expected. The energy-cost model, developed for comparative evaluation of battery cell chemistries in a commercial type pouch cell configuration, helps us to find the relationship between cost and energy density, enabling the prediction of the most promising material combinations for near-future non-aqueous rechargeable batteries for portable electronics and automotive applications. Among the wide variety of positive electrode materials only few show enough potential for commercialization, and, clearly, the immediate future will still be dominated by Li-ion technology, with Li-rich and Ni-rich materials as definite winners, and with Li–S and Na-ion emerging as contestants due to low cost and abundance of their key components. As further significant improvements in gravimetric/volumetric energy density and cost cannot be achieved through new battery chemistries, then the engineering, targeting cost reduction and safety assurance, will most likely be the main driving force behind future rechargeable battery development.